Composition for repairing cracks of concrete structure and method using the same

KR1020260132155APending Publication Date: 2026-09-02김광섭 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250024276
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2026-09-02

Smart Images

  • Figure 1020250024276
    Figure 1020250024276
Patent Text Reader

Abstract

The present invention relates to a composition for repairing cracks in concrete structures comprising Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, ethylene vinyl acetate resin powder, and a hydrophilically modified fiber reinforcement, and a repair method using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a composition for repairing cracks in concrete structures and a repair method using the same. Background Technology

[0002] Concrete is widely used to construct buildings or various civil engineering structures such as roads, bridges, ports, dams, tunnels, and circular pipes by mixing cement, aggregates, and water. However, as time passes while using these concrete structures, their durability and usability deteriorate over the long term due to salt damage, carbonation, alkali-aggregate reaction, biochemical corrosion, and corrosion expansion of steel caused by water penetration. Since the continued deterioration of these structures can eventually lead to their collapse, concrete structures must be continuously managed and repaired.

[0003] In particular, if the surface of a concrete structure deteriorates and spalling or cracking occurs, it facilitates the movement of deterioration factors and accelerates the progression of deterioration; therefore, to maintain the stability and performance of reinforced concrete structures, repairs must be carried out at the early stages of deterioration to suppress further progression, extend durability, and prevent performance degradation.

[0004] Meanwhile, Korean Registered Patent Publication No. 10-1763297 is presented as a similar prior art document regarding this. Prior art literature

[0005] Korean Patent Publication No. 10-1763297 (July 25, 2017) The problem to be solved

[0006] To solve the above-mentioned problems, the present invention aims to provide a composition for repairing cracks in concrete structures that has a uniform crack repair effect and excellent durability, and a repair method using the same.

[0007] However, the above purpose is exemplary, and the technical concept of the present invention is not limited thereto. means of solving the problem

[0008] One aspect of the present invention for achieving the above objective relates to a composition for repairing cracks in concrete structures, comprising Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, ethylene vinyl acetate resin powder, and a hydrophilically modified fiber reinforcement.

[0009] In one embodiment of the above, the composition for repairing cracks in the concrete structure may have a weight ratio of Portland cement: slag cement: expansive cement of 100:10 to 100:1 to 50.

[0010] In one embodiment above, the glycol-based compound may be one or more selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, polyethylene glycol, and polypropylene glycol.

[0011] In one embodiment above, the ethylene vinyl acetate resin may have a molar ratio of ethylene repeating units to vinyl acetate repeating units of 60:40 to 90:10.

[0012] In one embodiment above, the ethylene vinyl acetate resin may have a number average molecular weight of 100,000 to 300,000 g / mol.

[0013] In one embodiment above, the hydrophilically modified fiber reinforcement may be a polypropylene fiber coated with polyvinyl alcohol.

[0014] In one embodiment of the above, the polypropylene fiber may be pretreated with an oxidizing agent.

[0015] In addition, another aspect of the present invention comprises a) a step of removing foreign substances from a floor surface or wall surface to be constructed; b) a step of smoothing the surface of cracks of a certain size or larger on the floor surface or wall surface with putty or sealant; and c) a step of applying a composition for repairing cracks in concrete structures to the surface-straightened floor surface or wall surface.

[0016] The above-described composition for repairing cracks in concrete structures comprises Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, polymer resin powder, and hydrophilically modified fiber reinforcement, and the present invention relates to a repair method using the composition for repairing cracks in concrete structures, wherein the specific types of each component may be the same as those described above. Effects of the invention

[0017] The composition for repairing cracks in concrete structures and the repair method using the same according to the present invention improve strength and durability through the combination of Portland cement, slag cement, expansive cement, etc., fly ash and silica fume improve the microstructure to provide long-term chemical resistance, and a hydrophilically modified fiber reinforcement and ethylene vinyl acetate resin powder are mixed to increase crack resistance and toughness, thereby providing a uniform repair effect and excellent durability. Specific details for implementing the invention

[0018] The composition for repairing cracks in concrete structures and the repair method using the same according to the present invention will be described in detail below. The drawings presented below are provided as examples to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art. Accordingly, the present invention is not limited to the drawings presented below and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. Unless otherwise defined, technical and scientific terms used hereto have the meaning commonly understood by those skilled in the art to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the present invention are omitted in the following description and attached drawings.

[0019] One aspect of the present invention relates to a composition for repairing cracks in concrete structures, comprising Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, ethylene vinyl acetate resin powder, and a hydrophilically modified fiber reinforcement.

[0020] As such, the composition for repairing cracks in concrete structures according to the present invention has the advantage of improving strength and durability through the combination of Portland cement, slag cement, expansive cement, etc., providing long-term chemical resistance by improving the microstructure with fly ash and silica fume, and increasing crack resistance and toughness by mixing hydrophilically modified fiber reinforcement and ethylene vinyl acetate resin powder, thereby providing a uniform repair effect and excellent durability.

[0021] Hereinafter, each component of the composition for repairing cracks in concrete structures according to one example of the present invention will be described in more detail.

[0022] First, the composition for repairing cracks in concrete structures according to the present invention may use a mixture of three types of cement, thereby improving strength and durability when repairing structures. As described above, the cement is used by mixing Portland cement, slag cement, and expansive cement. In a preferred example, the weight ratio of Portland cement: slag cement: expansive cement may be 100:10 to 100:1 to 50, more preferably the weight ratio of Portland cement: slag cement: expansive cement may be 100:30 to 80:5 to 40, even more preferably the weight ratio of Portland cement: slag cement: expansive cement may be 100:50 to 70:10 to 30, and even more preferably the weight ratio of Portland cement: slag cement: expansive cement may be 100:55 to 65:15 to 25. The effect of improving strength and durability can be best within this range.

[0023] The aforementioned Portland cement is a type of cement widely used worldwide. It primarily hardens and develops strength through a chemical reaction (hydration) when mixed with water, and due to these characteristics, it is used in various structures. Its main components include calcium trisilicate, which provides initial strength; calcium dioxide, which is responsible for long-term strength; calcium aluminum trioxide, which rapidly increases initial strength but has low chemical resistance; and calcium iron tetroxide, which controls color and influences the hardening process. Due to this combination, Portland cement provides high durability and compressive strength.

[0024] The aforementioned slag cement is manufactured by finely grinding blast furnace slag generated during the steelmaking process. It is used in combination with Portland cement and features superior chemical resistance and durability compared to conventional Portland cement. Slag cement is primarily used in environments requiring resistance to salt damage, sulfuric acid penetration, and chloride ion penetration. Its low heat of hydration minimizes cracking even in large structures. Furthermore, due to the inherent properties of slag, it effectively improves the long-term strength of concrete.

[0025] The aforementioned expansive cement is a special cement that compensates for shrinkage by inducing microscopic expansion during hardening, making it effective in suppressing crack formation caused by drying shrinkage or temperature changes in concrete structures. Expansive cement is primarily used in large concrete structures where cracking is a concern or in structures where waterproofing is critical; the expansion occurring during the hydration process balances internal stresses, thereby providing dimensional stability. Through this, it possesses characteristics that enhance crack resistance and long-term structural stability.

[0026] In one example of the present invention, the fly ash is a byproduct composed of fine particles generated when burning coal, and is primarily used as a cement substitute and a concrete admixture. Fly ash possesses pozzolanic properties, which promote the hydration reaction when mixed with cement, thereby enhancing the strength and durability of repair structures. Furthermore, fly ash improves the workability of concrete and lowers the heat of hydration, contributing to the suppression of cracks that may occur in large structures. In particular, it plays a role in improving the long-term durability of structures by increasing resistance to chloride penetration and chemical resistance.

[0027] Such fly ash can be added in an amount of 5 to 35 parts by weight, more preferably 10 to 30 parts by weight, and even more preferably 15 to 25 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, the effect of improving high strength and chemical resistance is excellent; if too little is added, it is difficult to achieve the desired effect, and if too much is added, workability may be reduced.

[0028] In one example of the present invention, the silica fume is a material in the form of very fine spherical particles generated as a byproduct during the manufacturing process of metallic silicon or silicon alloys, and is mainly used to improve the strength and durability of repair structures. The silica fume has a high specific surface area, which fills the empty spaces between cement particles and promotes the hydration reaction of cement to form a very dense structure. Through this, it plays a role in improving the strength, chemical resistance, and water resistance of the crack repair composition.

[0029] Such silica fume can be added in an amount of 1 to 15 parts by weight, more preferably 3 to 12 parts by weight, and even more preferably 5 to 10 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, the effect of improving durability and strength through pozzolanic reaction is excellent; if too little is added, it is difficult to achieve the desired effect, and if too much is added, the heat of hydration can be reduced, but the development of early strength may be lowered.

[0030] In one example of the present invention, the metakaolin is a pozzolanic material manufactured using kaolin treated at high temperatures as a raw material, and plays a role in promoting a hydration reaction through a reaction with cement and improving the microstructure of the repair structure. Metakaolin increases the initial strength of the repair structure and can significantly improve durability by enhancing resistance to chloride ion penetration and alkali-silica reactions. In addition, due to its fine particles, homogeneous mixing is possible and it contributes to suppressing shrinkage of the repair structure.

[0031] Such metakaolin can be added in an amount of 1 to 25 parts by weight, more preferably 3 to 20 parts by weight, and even more preferably 5 to 15 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, it improves strength and durability and has an excellent effect of suppressing alkali-silica reactions; if too little is added, it is difficult to achieve the desired effect, and if too much is added, the repair structure may become too hard.

[0032] In one example of the present invention, the perlite is a lightweight material obtained by processing natural volcanic rock and is primarily used to reduce the density of repair structures and improve thermal insulation performance. Perlite has a porous structure, which can improve the workability of repair structures and reduce drying shrinkage when mixed. In addition, it has high chemical stability and can be used under various environmental conditions.

[0033] Such perlite can be added in an amount of 5 to 35 parts by weight, more preferably 10 to 30 parts by weight, and even more preferably 15 to 25 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, the effects of lightweighting and improved thermal insulation performance are excellent, and drying shrinkage can be effectively reduced; if too little is added, it is difficult to achieve the desired effect, and if too much is added, the strength may decrease.

[0034] In one example of the present invention, the glycol-based compound is used as an additive to suppress moisture evaporation and prevent drying shrinkage during the curing process of a crack repair composition, and primarily serves to improve the workability of the crack repair composition by imparting plastic properties. The glycol-based compound contributes to increasing the fluidity of the crack repair composition upon mixing, suppressing crack formation, and providing long-term durability. As a result, workability during the construction process is improved and the quality of the repaired structure is enhanced.

[0035] As a more specific example, the glycol-based compound may be one or more selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, polyethylene glycol, and polypropylene glycol.

[0036] Such glycol-based compounds may be added in an amount of 0.1 to 5 parts by weight, more preferably 0.3 to 3 parts by weight, and even more preferably 0.5 to 2 parts by weight per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, the effect of improving fluidity and workability is excellent; if too little is added, it is difficult to achieve the desired effect, and if too much is added, the strength may decrease.

[0037] In one example of the present invention, the ethylene vinyl acetate resin powder serves as a polymer-based additive that improves the flexibility and adhesion of concrete. The ethylene vinyl acetate resin powder increases crack resistance while maintaining the strength of the repair structure and is particularly useful in repair work requiring adhesion and waterproofing. Additionally, it has the effect of improving the durability of the structure by increasing impact resistance through interaction with cement. In a preferred example, the molar ratio of ethylene repeating units to vinyl acetate repeating units of the ethylene vinyl acetate resin may be 60:40 to 90:10, and more preferably 70:30 to 80:20. Furthermore, the number average molecular weight of the ethylene vinyl acetate resin may be 100,000 to 300,000 g / mol, and more preferably 120,000 to 200,000 g / mol. Within this range, not only can waterproofing, flexibility, and adhesion be further improved, but excellent durability can also be provided.

[0038] Such ethylene vinyl acetate resin can be added in an amount of 0.1 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, and even more preferably 1 to 5 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, the effect of improving flexibility and adhesion is excellent; if too little is added, it is difficult to achieve the desired effect, and if too much is added, it may have a negative effect on shrinkage and crack resistance.

[0039] In one example of the present invention, the hydrophilically modified fiber reinforcement is a material in which the bonding strength with the cement matrix is ​​strengthened by treating the fiber reinforcement to be hydrophilic, and it serves to suppress microcracks within repair structures and improve initial strength and durability. Such fiber reinforcement has the effect of improving the long-term performance of concrete by retaining the moisture necessary for the hydration reaction and reducing the occurrence of cracks caused by shrinkage and expansion.

[0040] As a more specific example, the hydrophilically modified fiber reinforcement described above may be polypropylene fibers coated with polyvinyl alcohol. As such, polypropylene fibers coated with polyvinyl alcohol increase the bonding strength with the cement matrix, thereby improving crack resistance and toughness, and maintain durability even in alkaline environments, providing a long-term reinforcement effect. Additionally, it increases water absorption capacity to reduce cracking caused by drying shrinkage, and is even more effective in compositions containing fly ash and silica fume. When combined with polymer resin powder, it improves strength and impact resistance, and increases workability and uniformity due to the homogeneous distribution of fibers. In particular, the polyvinyl alcohol coating improves chemical resistance and environmental resistance, providing resistance to salt damage and acid damage, and is advantageous because it can enhance deformation resistance and dimensional stability when used with expansive cement.

[0041] In addition, the polyvinyl alcohol may have a number average molecular weight of 10,000 to 200,000 g / mol, and more preferably 50,000 to 150,000 g / mol. Within this range, it has a suitable viscosity so that it can be uniformly coated on the surface of the polypropylene fiber during the coating process, and can maintain durability and flexibility while strengthening the physical bond with the polypropylene fiber, thereby preventing the coating layer from peeling off easily.

[0042] Meanwhile, the polypropylene fiber coated with the polyvinyl alcohol may be pretreated to ensure that the polyvinyl alcohol is well coated on the surface of the polypropylene fiber; specifically, the polypropylene fiber may be pretreated with an oxidizing agent. Polypropylene is inherently hydrophobic and has almost no reactive functional groups on its surface, making direct coating difficult. However, when the polypropylene fiber is pretreated with an oxidizing agent, the hydrophobic surface is partially oxidized to generate hydrophilic functional groups, such as hydroxyl or carboxyl groups. This improves wettability, allowing the polyvinyl alcohol to be coated more uniformly and increasing adhesion. In this case, the oxidizing agent that can be used may be hydrogen peroxide.

[0043] The above-mentioned hydrophilically modified fiber reinforcement can be added in an amount of 0.1 to 5 parts by weight, more preferably 0.3 to 3 parts by weight, and even more preferably 0.5 to 2 parts by weight, per 100 parts by weight of cement (Portland cement, slag cement, and expansive cement). Within this range, it contributes to suppressing microcracks and improving strength; if too little is added, it is difficult to achieve the desired effect, and if too much is added, the fluidity of the mixture may decrease.

[0044] In addition, another aspect of the present invention comprises a) a step of removing foreign substances from a floor surface or wall surface to be constructed; b) a step of smoothing the surface of cracks of a certain size or larger on the floor surface or wall surface with putty or sealant; and c) a step of applying a composition for repairing cracks in concrete structures to the surface-straightened floor surface or wall surface.

[0045] The present invention relates to a repair method using a composition for repairing cracks in a concrete structure, wherein the composition for repairing cracks in a concrete structure comprises Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, polymer resin powder, and a hydrophilically modified fiber reinforcement.

[0046] First, a) a step of removing foreign substances from the floor or wall surface to be constructed is performed. This step is intended to remove foreign substances from the floor or wall surface to be constructed so that the composition can adhere well to the substrate, and can be performed according to methods commonly used in the industry. As a non-limiting example, to remove contaminants such as dust, dirt, oil, etc. attached to the floor or wall surface, the surface may be cleaned using a brush or vacuum cleaner, or if water washing is required, the surface may be washed using a high-pressure washer.

[0047] Next, b) a step of smoothing the surface of cracks of a certain size or larger on the floor or wall surface using putty or sealant is performed. This step is intended to flatten the surface by filling the cracks with putty or sealant, and can be carried out according to methods commonly used in the industry. As a non-limiting example, a spatula or putty knife may be used to fill the cracks with putty, or a sealant gun may be used to fill the cracks and then flatten the surface.

[0048] Next, c) the step of applying a composition for repairing cracks in concrete structures to a surface-finished floor or wall surface is performed. The crack repair composition is the same as described above and can be applied according to methods commonly used in the industry. The crack repair composition is thoroughly mixed before use, and the composition is applied uniformly to the floor or wall surface using a roller, brush, or spray gun. If necessary, the application may be performed one or more times.

[0049] In addition, a step of applying a primer may be further performed to increase the adhesion of the crack repair composition, and the primer may be one commonly used in the industry and may be applied using a roller or a brush.

[0051] Hereinafter, the composition for repairing cracks in concrete structures according to the present invention and the repair method using the same will be described in more detail through examples. However, the following examples are merely references for explaining the present invention in detail, and the present invention is not limited thereto and can be implemented in various forms.

[0052] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention. Additionally, units of additives not specifically stated in the specification may be in weight percent.

[0053] [Preparation Example 1] Hydrophilically modified fiber reinforcement (PVA-PP)

[0054] First, to introduce hydroxyl and carboxyl groups to the surface of hydrophobic polypropylene fibers, they were pretreated by immersing them in a 30 wt% aqueous hydrogen peroxide solution for 30 minutes, then thoroughly washed with distilled water and completely dried in an oven at 50°C.

[0055] Next, the pretreated polypropylene (PP) fiber was immersed for 10 minutes in an aqueous solution in which polyvinyl alcohol (PVA) with a number average molecular weight of 85,000 g / mol was dissolved at a concentration of 5 wt% to allow sufficient adsorption of PVA onto the PP surface, and then dried in an oven at 50°C for 2 hours to completely cure the PVA.

[0056] [Preparation Example 2] Hydrophilically modified fiber reinforcement

[0057] A pretreated polypropylene (PP) fiber was immersed for 10 minutes in an aqueous solution in which polyvinyl alcohol (PVA) with a number average molecular weight of 85,000 g / mol was dissolved at a concentration of 5 wt% without pretreatment to allow sufficient adsorption of PVA onto the PP surface, and then dried in an oven at 50°C for 2 hours to completely cure the PVA.

[0058] [Examples 1 to 5]

[0059] A crack repair composition was prepared by mixing fly ash, silica fume, metakaolin, perlite, propylene glycol, ethylene vinyl acetate resin powder (EVA, 70 mol% ethylene repeating unit, number average molecular weight 140,000 g / mol), and the hydrophilically modified fiber reinforcement of Preparation Example 1 (PVA-PP) as shown in Table 1 below with respect to 100 parts by weight of cement mixed with 50 parts by weight of Portland cement, 30 parts by weight of slag cement, and 20 parts by weight of expansive cement.

[0060] [Example 6]

[0061] All processes were carried out in the same manner as in Example 3, except that the hydrophilically modified fiber reinforcement of Preparation Example 2 was used instead of the hydrophilically modified fiber reinforcement of Preparation Example 1.

[0062] [Comparative Example 1]

[0063] Each component was mixed in the same manner as in Example 3 above, but unmodified polypropylene fibers were used instead of the hydrophilically modified fiber reinforcement of Preparation Example 1.

[0064] (Weight portion) cement Fly ash Silica fume Metakaolin Perlite Propylene glycol EVA PVA-PP Example 1 100 5 1 1 5 0.1 0.1 0.1 Example 2 100 10 3 3 10 0.3 0.5 0.3 Example 3 100 20 8 10 20 1 3 1 Example 4 100 30 12 20 30 3 8 3 Example 5 100 35 15 25 35 5 10 5 Example 6 100 20 8 10 20 1 3 1 (Preparation Example 2) Comparative Example 1 100 20 8 10 20 1 3 1(PP)

[0065] [Physical Property Evaluation]

[0066] Specimens were prepared using the crack repair compositions prepared in the above examples and comparative examples, and tests were conducted on the specimens for compressive strength, adhesion strength, flexural strength, change in length, and cracking resistance. The tests were performed according to KS test methods (strength KS F 4042, change in length KS F 2424, cracking resistance KS F 4937), and the results are shown in Table 2 below.

[0067] (Weight portion) Compressive strength (N / mm²) Adhesion strength (N / mm²) Flexural strength (N / mm²) Rate of change in length (%) Cracked Example 1 51.2 1.65 8.3 0.032 Microcracks occur Example 2 52.3 1.72 8.5 0.025 No cracks Example 3 52.8 1.76 8.9 0.021 No cracks Example 4 54.1 1.78 8.8 0.022 No cracks Example 5 54.5 1.79 8.7 0.025 No cracks Example 6 52.2 1.71 8.5 0.026 No cracks Comparative Example 1 51.7 1.69 8.4 0.028 Microcracks occur

[0068] Referring to Tables 1 and 2 above, it was confirmed that when Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, ethylene vinyl acetate resin powder, and hydrophilically modified fiber reinforcement are mixed in appropriate proportions according to the present invention, excellent strength characteristics and crack resistance are obtained.

[0069] Although the present invention has been described above through specific details and limited embodiments, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

[0070] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.

Claims

Claim 1 A composition for repairing cracks in concrete structures comprising Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, ethylene vinyl acetate resin powder, and hydrophilically modified fiber reinforcement. Claim 2 In claim 1, the composition for repairing cracks in a concrete structure is a composition for repairing cracks in a concrete structure having a weight ratio of Portland cement: slag cement: expansive cement of 100:10 to 100:1 to 50. Claim 3 A composition for repairing cracks in a concrete structure according to claim 1, wherein the glycol-based compound is one or more selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, polyethylene glycol, and polypropylene glycol. Claim 4 A composition for repairing cracks in concrete structures according to claim 1, wherein the ethylene vinyl acetate resin has a molar ratio of ethylene repeating units to vinyl acetate repeating units of 60:40 to 90:

10. Claim 5 A composition for repairing cracks in concrete structures, wherein the ethylene vinyl acetate resin has a number average molecular weight of 100,000 to 300,000 g / mol in claim 4. Claim 6 A composition for repairing cracks in concrete structures, wherein the fiber reinforcement is a polypropylene fiber coated with polyvinyl alcohol in claim 1. Claim 7 A composition for repairing cracks in concrete structures according to claim 6, wherein the polypropylene fibers are pretreated with an oxidizing agent. Claim 8 a) a step of removing foreign substances from a floor surface or wall surface to be constructed; b) a step of smoothing the surface of cracks of a certain size or larger on the floor surface or wall surface with putty or sealing; and c) a step of applying a composition for repairing cracks in a concrete structure to the surface-straightened floor surface or wall surface; wherein the composition for repairing cracks in a concrete structure comprises Portland cement, slag cement, expansive cement, fly ash, silica fume, metakaolin, perlite, glycol-based compound, polymer resin powder, and a hydrophilically modified fiber reinforcement. A repair method using a composition for repairing cracks in a concrete structure. Claim 9 In claim 8, a repair method using a composition for repairing cracks in a concrete structure, wherein the composition for repairing cracks in the concrete structure has a weight ratio of Portland cement: slag cement: expansive cement of 100:10 to 100:1 to 50. Claim 10 A repair method using a composition for repairing cracks in a concrete structure according to claim 8, wherein the glycol-based compound is one or more selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, polyethylene glycol, and polypropylene glycol. Claim 11 A repair method using a composition for repairing cracks in a concrete structure, wherein the ethylene vinyl acetate resin has a molar ratio of ethylene repeating units to vinyl acetate repeating units of 60:40 to 90:

10. Claim 12 A repair method using a composition for repairing cracks in a concrete structure, wherein the ethylene vinyl acetate resin has a number average molecular weight of 100,000 to 300,000 g / mol in claim 11. Claim 13 A repair method using a composition for repairing cracks in a concrete structure, wherein the fiber reinforcement is a polypropylene fiber coated with polyvinyl alcohol, in claim 8. Claim 14 A repair method using a composition for repairing cracks in concrete structures according to claim 13, wherein the polypropylene fibers are pretreated with an oxidizing agent.